Educação e contra-hegemonia na década neoliberal: as tendências pedagógicas contra-hegemônicas entre a crise paradigmática e a construção de outra hegemonia possível no limiar do século XXI - Manfredi, Maria Noemi Gonçalves do Prado (2014)
This PhD thesis has as object the counter-hegemonic field in education in the Neoliberal Decade analyzed by historical and polítical aspects, oriented by bibliographical research and deep interviews with theoretical-educators: Dermeval Saviani (Historical-Critical Pedagogy), José Carlos Libâneo ( Critical-Social Pedagogy of Contents), Oder José dos Santos (Practice Pedagogy, or Social Conflicts Pedagogy) and Lisete Regina Gomes Arelaro (Liberating Pedagogy by Paulo Freire). The theoretical and methodological treatment, in a dialectical conception, presents different ways to be counter-hegemonic from the conflict of ideas between the different and not between the antagonistic, showing the social and polítical role of the education for the social transformation. The analytic category as reference for this study development is hegemony/counter-hegemony by Antonio Gramsci and Boaventura de Sousa Santos. The relevance of the investigation the theme is justified as support for counterhegemonic movement future analyzes in education in Brazil and for the new educators generation